2021
DOI: 10.1016/j.psj.2021.101020
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Evaluation of the incidence of white striping and underlying myopathic abnormalities affected by fast weight gain in commercially fed broiler chickens

Abstract: Significant improvements in genetics, nutrition, and food efficiency have had a great impact on the rapid growth of broilers, notably with increases in muscle mass. However, with rapid growth, the broiler industry has been negatively impacted by the increased incidence of myopathies, including white striping. White striping affects the pectoralis major muscle of broilers, particularly the larger breasts of rapidly growing modern commercial broiler lines. In this study, we documented the growth process of comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 10 publications
3
12
0
Order By: Relevance
“…In line with the previous reports of Kuttappan et al ., 55 Prisco et al ., 22 and Vanhatalo et al ., 62 myofibers of broiler chickens fed control diets were surrounded or infiltrated by lymphohistiocytic cells. Immunohistochemistry revealed that the inflammatory cells were mostly macrophages.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In line with the previous reports of Kuttappan et al ., 55 Prisco et al ., 22 and Vanhatalo et al ., 62 myofibers of broiler chickens fed control diets were surrounded or infiltrated by lymphohistiocytic cells. Immunohistochemistry revealed that the inflammatory cells were mostly macrophages.…”
Section: Discussionsupporting
confidence: 92%
“…Increased lipidosis was noted in control group as shown in earlier studies 22,55,62 . The exact mechanism of lipid accumulation is not fully understood yet.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The White Striping (WS) is one of the most prevalent myopathies occurring in modern commercial broilers nowadays, which is characterized macroscopically by parallel white fatty striations across the muscle fibers on the surface of breast fillets and thighs ( Kuttappan et al, 2013 ). The most prominent histological features associated to this condition are myodegeneration with regeneration, perivascular necrosis, interstitial inflammation, lipidosis, and infiltration of connective tissue ( Kuttappan et al, 2013 ; Sihvo et al, 2014 ; Russo et al, 2015 ; Vanhatalo et al, 2021 ). From a meat quality standpoint, the WS disorder represents a huge economic impact on the chicken industry, since it affects the most valuable part of the broiler carcass, increasing the downgrading percentages and condemnation of breast fillets.…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that genetic selection of commercial broilers for fast growth increases the incidence of myopathies, and a number of factors have been associated with the onset and severity of WS, such as genotype (high breast yield), gender (males), fast growth rate, heavy weight of the Pectoralis major , and diets with high energy ( Petracci et al, 2013 ; Mutryn et al, 2015 ; Trocino et al, 2015 ; Cruz et al, 2017 ; Griffin et al, 2018 ; Vanhatalo et al, 2021 ). Different causative mechanisms for WS occurrence have been suggested to date: hypoxia, oxidative stress, fiber-type switching, disruption in satellite cells proliferation and differentiation, metabolic disorders, and nutritional deficiencies, but no conclusive evidence was found regarding the etiology of this disorder ( Russo et al, 2015 ; Daughtry et al, 2017 ; Boerboom et al, 2018 ; Marchesi et al, 2019 ; Soglia et al, 2019 ; Abasht et al, 2021 ; Lake et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%